CHARACTERISTIСS OF THE LIPID PROFILE AT PATIENTS WITH TYPE 2 DIABETES MELLITUS COMPLICATED WITH STEATOSIS - N. A. Kuzmenko; A. S. Sultanmuradova (Медицинский вестник Юга России, 2013)
Purpose: To study dynamics of a lipidic profile at patients with diabetes 2 types, against combination application of exenatide and metformin.Materials and methods: Research is conducted on 87 patients with diabetes 2 types complicated steatosis. All patients received general clinical research such as lipidogram.Results: In the course of treatment patients had a decrease in atherogenous fractions of the cholesterol, more expressed at treatment metformin and combinations metformin with the exenatide. The combination metformin with preparations sulfonylurea concerning correction of indicators of a lipidic exchange was less effective.Summary: more effective constrain hypertriglyceridemia as a risk factor for steatosis observed with metformin and exenatide.